2019
DOI: 10.1021/acsanm.8b02114
|View full text |Cite
|
Sign up to set email alerts
|

Phase Behavior of cistrans Mixtures of Double-Decker Shaped Silsesquioxanes for Processability Enhancement

Abstract: Closed double-decker shaped silsesquioxanes (DDSQ-(Ph)8-2­((Me)­(R))) with R as phenyl, para-phenylamine, and para-phenylethynyl phenyl were synthesized. Isolation of nearly pure trans and cis isomers was obtained by fractional recrystallization. Crystallographic and thermal characteristics of these isolated isomers were obtained by X-ray diffraction of a single crystal and differential scanning calorimetry (DSC). It was observed that melting temperature increases as the size of the R group decreases from para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 67 publications
0
21
0
Order By: Relevance
“…Once separated, it was demonstrated that cis DDSQ-2(RR') has a different crystallographic structure than trans DDSQ-2(RR') as well as different thermal and physical properties [4,5,19].…”
Section: Scheme 1 Functionalization Of Ddsq-oh 4 With Dichlorosilanesmentioning
confidence: 99%
See 4 more Smart Citations
“…Once separated, it was demonstrated that cis DDSQ-2(RR') has a different crystallographic structure than trans DDSQ-2(RR') as well as different thermal and physical properties [4,5,19].…”
Section: Scheme 1 Functionalization Of Ddsq-oh 4 With Dichlorosilanesmentioning
confidence: 99%
“…Recently, the phase behavior of cis and trans DDSQ-2(RR') binary mixtures where R was methyl and R' was phenyl, aniline, or 1,4-phenylethynyl(phenyl) was reported [19]. From the study, it was determined that the bulkier moiety has a reductive effect on the melting temperature of isolated cis and trans isomers.…”
Section: Scheme 1 Functionalization Of Ddsq-oh 4 With Dichlorosilanesmentioning
confidence: 99%
See 3 more Smart Citations